1991
DOI: 10.1111/j.1523-1739.1991.tb00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Flying Foxes (Chiroptera: Pteropodidae): Threatened Animals of Key Ecological and Economic Importance

Abstract: Flying foxes are animals of extraordinary ecological and economic importance throughout forests of the Old World tropics Nearly 200 species play an essential role as forest pollinators and seed dispersers, yet they are frequently misunderstood intensely persecuted and exceptionally vulnerable to extinction Their role in the propagation of numerous important plants remains virtually uninvestigated. However, our review of already available literature demonstrates that at least 289 plant species rely to vatying d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
257
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(272 citation statements)
references
References 27 publications
3
257
0
4
Order By: Relevance
“…Fossil evidence indicates the majority of Polynesian bird and bat species became extinct or were extirpated in the wake of human colonisation (Steadman 1993(Steadman , 1995Koopman and Steadman 1995). Indigenous Polynesian island fruit bats and birds are key pollinators and seed dispersers of native rainforest flora (Fujita and Tuttle 1991;Cox et al 1991;McConkey and Drake 2002;Meehan et al 2002;). Koopman and Steadman (1995) suggested that a loss of vertebrate frugivores in Polynesia will lead to a decline in plant diversity, and indeed fossil pollen data from Tonga indicate that diminished rainforest plant diversity accompanied the loss of native dispersers and pollinators .…”
Section: Discussionmentioning
confidence: 99%
“…Fossil evidence indicates the majority of Polynesian bird and bat species became extinct or were extirpated in the wake of human colonisation (Steadman 1993(Steadman , 1995Koopman and Steadman 1995). Indigenous Polynesian island fruit bats and birds are key pollinators and seed dispersers of native rainforest flora (Fujita and Tuttle 1991;Cox et al 1991;McConkey and Drake 2002;Meehan et al 2002;). Koopman and Steadman (1995) suggested that a loss of vertebrate frugivores in Polynesia will lead to a decline in plant diversity, and indeed fossil pollen data from Tonga indicate that diminished rainforest plant diversity accompanied the loss of native dispersers and pollinators .…”
Section: Discussionmentioning
confidence: 99%
“…An indicator species is one whose presence, absence, and condition is suggestive of environmental health (Noss 1990). Since bats provide many ecosystem functions, such as pollination and seed dispersal, they are intrinsically linked to plant populations where they live (Fujita and Tuttle 1991;McConkey and Drake 2006). The predation of bats on insects may also reflect arthropod abundance and species diversity (Kalka et al 2008).…”
Section: Inventory and Monitoring Programsmentioning
confidence: 99%
“…The importance of flying foxes as seed dispersers comes in large part from aspects of their physiology: flight allows them to routinely transport seeds over large distances, and their large size (sometimes with wingspans approaching 2 m) allows large fruit to be carried. However, they face strong mortality from humans, being hunted for sport and food, sold commercially as a luxury food item, and killed by farmers protecting fruit trees [49]. Some flying fox species have already been driven extinct by humans.…”
Section: Are Animal Seed Dispersers Important To Plant Conservation?mentioning
confidence: 99%